소방관의 우울, 불안, ADHD, 충동성 - 신재권; 김지선; 임명호; 이재원; 김경민; 이표규; 오성범; 양영애; 백기청; Shin, Jae Kwon; Kim, Ji Sun; Lim, Myung Ho; et al. (Anxiety and mood, 2017)
Objective : This study aimed to evaluate the association of exhaustion, ADHD, self-esteem, impulsivity, suicidal tendencies and quality of life as well as depression and anxiety in fire officers in Korea. Methods : This study was undertaken for the first time in Korea, from September 2016 to December 2016. A set of questionnaires was provided to a total of 113 fire officers and 284 other participants as a comparison group. All subjects were evaluated using the Beck's Depression Inventory, Beck's Anxiety Inventory, Malach Burnout Inventory, Korean Adult Attention Deficit Hyperactivity Disorder Scales, Rosenberg's Self-esteem Inventory, Baratt's Impulsivity Scale, Beck's Scale of Suicide Ideation, and Quality of Life Scale. Furthermore, the odds ratio of depression, anxiety, exhaustion, ADHD, self-esteem, impulsivity, suicidal tendency and quality of life were evaluated the fire officer group and control group were compared through logistic regression analysis. Result : The results of this study indicated that the fire officers were more likely to show depression, anxiety, exhaustion, ADHD, low self-esteem and higher impulsivity. Also, the association between the fire officer group and depression, ADHD and impulsivity was confirmed through logistic regression analysis. Conclusion : Timely and effective evaluation and treatment of impulsivity, as well as depression is required for fire officers.